2020
DOI: 10.3390/genes11091095
|View full text |Cite
|
Sign up to set email alerts
|

Population Divergence along a Genetic Line of Least Resistance in the Tree Species Eucalyptus globulus

Abstract: The evolutionary response to selection depends on the distribution of genetic variation in traits under selection within populations, as defined by the additive genetic variance-covariance matrix (G). The structure and evolutionary stability of G will thus influence the course of phenotypic evolution. However, there are few studies assessing the stability of G and its relationship with population divergence within foundation tree species. We compared the G-matrices of Mainland and Island population groups of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 105 publications
(233 reference statements)
0
7
0
Order By: Relevance
“…Second, the two species may differ in their patterns of climate adaptation due to different patterns of correlated evolutionary changes among the focal traits during species divergence (i.e., evolutionary integration [ 21 , 22 , 67 ]). In addition, for a given species, genetic constraints associated with genetic architecture within populations may have influenced the course of phenotypic evolution and adaptive diversification of the conspecific populations [ 68 , 69 , 70 ]. It is also possible that, within a species, differences among populations in natural selection may have shaped the genetic (co)variance patterns within populations over evolutionary time, thus leading to an alignment between genetic architecture and population trajectories [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the two species may differ in their patterns of climate adaptation due to different patterns of correlated evolutionary changes among the focal traits during species divergence (i.e., evolutionary integration [ 21 , 22 , 67 ]). In addition, for a given species, genetic constraints associated with genetic architecture within populations may have influenced the course of phenotypic evolution and adaptive diversification of the conspecific populations [ 68 , 69 , 70 ]. It is also possible that, within a species, differences among populations in natural selection may have shaped the genetic (co)variance patterns within populations over evolutionary time, thus leading to an alignment between genetic architecture and population trajectories [ 71 , 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative genetic studies of these trials identified significant popula-tion differentiation in numerous traits, which was summarised by partitioning the gene pool into 13 geographic races [49]. While there are likely evolutionary constraints [52], population differences have been shown to: occur at multiple geographic scales, from hundreds of metres [53,54] to hundreds of kilometres [49,55], be adaptive (i.e., significant population × environment interactions for growth in common garden trials, [32]), and even to have extended community-level consequences [56,57]. Numerous traits exhibit clines with latitude and climate as well as signals of divergent selection (Q ST > F ST ) [47,49,58,59].…”
Section: Study Speciesmentioning
confidence: 99%
“…The current adaptive differences among the E. globulus provenances are a result of historical selection and constraints [52]. Our RDA analysis allowed the identification of the independent climate vectors most likely to have historically contributed to shaping the genomic adaptation in these provenances.…”
Section: Climate Variables Driving Genomic Adaptationmentioning
confidence: 99%
“…Tree adaptation to major environmental gradients such as aridity is polygenic and genome-wide (Kramer et al, 2015;Jordan et al, 2017;Steane et al, 2017), involves diverse functional traits (Alberto et al, 2013;Kremer et al, 2014), and potentially also genetic constraints (Bourne et al, 2017;Costa e Silva et al, 2020). Detecting adaptive changes in local populations of longlived organisms, such as forest trees, is difficult due to numerous factors (Alberto et al, 2013), including long-life cycles (Petit and Hampe, 2006), ontogenetic (Brunner et al, 2016) and plastic (Nicotra et al, 2010;McLean et al, 2014) changes in phenotype, superimposed on the normal selective filtering of mal-adapted inbred progeny during stand development (Koelewijn et al, 1999;Costa e Silva et al, 2011;Griffin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%